Pengaruh Nilai Kerja terhadap Kinerja Lingkungan di Bandara - TADJOEDIN, ACHMAD RAMZY; MANGKUPRAWIRA, SYAFRI; SUMARDJO, SUMARDJO; SAEFUDDIN, ASEP (UI Scholars Hub, 2011)
This study aimed to formulate strategies that need to be done to improve the environmental performance of the airport. The research uses survey methods to acquire data about the factors that affect the environmental performance improvement strategies in Angkasa Pura I airport. The data are analyzed by using regression analysis techniques, needs analysis, and prospective analysis. The results of the analysis show that: (1) respondents who are concerned about environmental performance within the company reached an average of 4.12 (care) and within the environment outside the company reached an average of 4.07 (care); (2) the needs of stakeholders for environmental quality inside and outside the company are: the improvement of airport performance; efficient, distinct, precise, and customer-ease-oriented services; improvement of airport officials’ professionalism; socialization of clear and firm rules and legal enforcement for the employees and customers; development of airport facilities and its supporting access; and (3) the key successes underlying the improvement of airport performance within and outside company in the future are leadership, cleanliness, caring, modesty, and service-oriented attitude.